Dari budaya untuk pendidikan: Peran tradisi Wuat wa’i dalam mendukung pendidikan di Manggarai - Odilia Cecen; Mamuriah Mamuriah; Inayah Inayah (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2026)
Education plays a vital role in developing human resources, yet it is often separated from its cultural roots. This study aims to describe the role and meaning of the Wuat Wa’I tradition in Manggarai as a form of social support in promoting education. The research was conducted using a library research method by reviewing various relevant literature. The findings show that this tradition is not merely a ritual, but also a means of instilling noble values, providing material and moral support, and serving as a harmonious bridge between culture and education. It has proven effective in shaping individuals who are both intellectually capable and possess strong character.